Knockout of Adamts7, a Novel Coronary Artery Disease Locus in Humans, Reduces Atherosclerosis in Mice. Issue 13 (31st March 2015) - Bauer, Robert C.; Tohyama, Junichiro; Cui, Jian; Cheng, Lan; Yang, Jifu; Zhang, Xuan; Ou, Kristy; Paschos, Georgios K.; Zheng, X. Long; Parmacek, Michael S.; Rader, Daniel J.; Reilly, Muredach P.
<x xml:space="preserve">Abstract</x> Background— Genome-wide association studies have established ADAMTS7 as a locus for coronary artery disease in humans. However, these studies fail to provide directionality for the association between ADAMTS7 and coronary artery disease. Previous reports have implicated ADAMTS7 in the regulation of vascular smooth muscle cell migration, but a role for and the direction of impact of this gene in atherogenesis have not been shown in relevant model systems. Methods and Results— We bred an Adamts7 whole-body knockout mouse onto both the Ldlr and Apoe knockout hyperlipidemic mouse models. Adamts7−/−/Ldlr−/− and Adamts7−/−/Apoe−/− mice displayed significant reductions in lesion formation in aortas and aortic roots compared with controls. Adamts7 knockout mice also showed reduced neointimal formation after femoral wire injury. Adamts7 expression was induced in response to injury and hyperlipidemia but was absent at later time points, and primary Adamts7 knockout vascular smooth muscle cells showed reduced migration in the setting of tumor necrosis factor-α stimulation. ADAMTS7 localized to cells positive for smooth muscle cell markers in human coronary artery disease lesions, and subcellular localization studies in cultured vascular smooth muscle cells placed ADAMTS7 at the cytoplasm and cell membrane, where it colocalized with markers of podosomes. Conclusions— These data represent the first in vivo experimental validation of the association of Adamts7 with atherogenesis, likely through modulation of vascular cell migration and matrix in atherosclerotic lesions. These results demonstrate that Adamts7 is proatherogenic, lending directionality to the original genetic association and supporting the concept that pharmacological inhibition of ADAMTS7 should be atheroprotective in humans, making it an attractive target for novel therapeutic interventions.